2014
DOI: 10.1002/mnfr.201400639
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-oligosaccharides may directly enhance intestinal barrier function through the modulation of goblet cells

Abstract: Collectively, the data indicate that GOS may enhance mucosal barrier function through direct stimulation of intestinal goblet cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 49 publications
3
91
1
1
Order By: Relevance
“…This mechanism may be important in reducing the extent of gastric mucosal damage caused by the administration of NSAIDs [89]. In addition, after treating with prebiotic galacto-oligosaccharides (GOS), the expressions of MUC2 and TFF3 are significantly up-regulated (Table 2), which indicates that GOS may enhance mucosal protective function via direct stimulation of intestinal goblet cells [90].…”
Section: Gastrin Nsaids and Gos Upregulate The Expression Of Tff2/ Tff3mentioning
confidence: 98%
“…This mechanism may be important in reducing the extent of gastric mucosal damage caused by the administration of NSAIDs [89]. In addition, after treating with prebiotic galacto-oligosaccharides (GOS), the expressions of MUC2 and TFF3 are significantly up-regulated (Table 2), which indicates that GOS may enhance mucosal protective function via direct stimulation of intestinal goblet cells [90].…”
Section: Gastrin Nsaids and Gos Upregulate The Expression Of Tff2/ Tff3mentioning
confidence: 98%
“…GOS also has effects on intestinal epithelial cells and has been reported to stimulate gut barrier function (Bhatia et al 2015). An in vitro study by Bhatia et al (Bhatia et al 2015) showed that GOS enhanced intestinal barrier function through modulation of the secretory function of human goblet cells by up regulation of related genes and protein expression (Bhatia et al 2015).…”
Section: Effects Of Gos On Epithelial Cells Responsesmentioning
confidence: 99%
“…An in vitro study by Bhatia et al (Bhatia et al 2015) showed that GOS enhanced intestinal barrier function through modulation of the secretory function of human goblet cells by up regulation of related genes and protein expression (Bhatia et al 2015). GOS can also stimulate in vitro tight junction assembly in gut intestinal human Caco-2 cells, which is beneficial for the integrity of the epithelial barrier (Akbari et al 2015).…”
Section: Effects Of Gos On Epithelial Cells Responsesmentioning
confidence: 99%
“…Effects of hMOSs were compared to effects of GOS, which is currently being applied in infant formula as a substitute for hMOs and known to enhance intestinal barrier function through the modulation of goblet cells . We examined gene expression alterations of the goblet cell secretory related genes MUC2 , TFF3 , and RETNLB , and the Golgi‐sulfotransferase genes CHST5 and GAL3ST2 in the human goblet cell line LS174T .…”
Section: Introductionmentioning
confidence: 99%